2017
DOI: 10.3389/fnmol.2017.00367
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Hepcidin Upregulation by Lipopolysaccharide in the Interleukin-6 Knockout Mouse Brain

Abstract: To find out whether the Interleukin-6 (IL-6)/signal transducer and activator of transcription 3 (STAT3) signaling pathway is involved in the expression of hepcidin in the mouse brain in vivo, we investigated the phosphorylation of STAT3, as well as the expression of hepcidin mRNA, ferroportin 1 (Fpn1) and ferritin light chain (Ft-L) proteins in the cortex and hippocampus of LPS-treated wild type (IL-6+/+) and IL-6 knockout (IL-6-/-) mice. We demonstrated that IL-6 knockout could significantly reduce the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 56 publications
(65 reference statements)
2
31
0
Order By: Relevance
“…In physiological conditions hepcidin expression in brain structures and cells (neurons, glial cells, endothelial cells, epithelial cells of choroid plexus) has been consistently observed by in vivo studies in humans and rodents, albeit in low levels ( Krause et al, 2000 ; Pigeon et al, 2001 ; Zechel et al, 2006 ; Wang et al, 2008 , 2010 ; Hänninen et al, 2009 ; Raha et al, 2013 ; Wei et al, 2014 ; Farajdokht et al, 2015 ; Raha-Chowdhury et al, 2015 ; Graf et al, 2016 ; Li Y. et al, 2016 ; Pan et al, 2016 ; Tan et al, 2016 ; Lu et al, 2017 ; You et al, 2017 ; Zhang et al, 2017 ). Data from human and animal studies suggest that local hepcidin is more robustly expressed in pathophysiological states ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ). Similar to other cells, hepcidin main target protein in brain cells is FPN, but also iron import proteins ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ).…”
Section: Brain Hepcidin Expression and Mechanisms Of Regulationmentioning
confidence: 83%
See 1 more Smart Citation
“…In physiological conditions hepcidin expression in brain structures and cells (neurons, glial cells, endothelial cells, epithelial cells of choroid plexus) has been consistently observed by in vivo studies in humans and rodents, albeit in low levels ( Krause et al, 2000 ; Pigeon et al, 2001 ; Zechel et al, 2006 ; Wang et al, 2008 , 2010 ; Hänninen et al, 2009 ; Raha et al, 2013 ; Wei et al, 2014 ; Farajdokht et al, 2015 ; Raha-Chowdhury et al, 2015 ; Graf et al, 2016 ; Li Y. et al, 2016 ; Pan et al, 2016 ; Tan et al, 2016 ; Lu et al, 2017 ; You et al, 2017 ; Zhang et al, 2017 ). Data from human and animal studies suggest that local hepcidin is more robustly expressed in pathophysiological states ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ). Similar to other cells, hepcidin main target protein in brain cells is FPN, but also iron import proteins ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ).…”
Section: Brain Hepcidin Expression and Mechanisms Of Regulationmentioning
confidence: 83%
“…Data from human and animal studies suggest that local hepcidin is more robustly expressed in pathophysiological states ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ). Similar to other cells, hepcidin main target protein in brain cells is FPN, but also iron import proteins ( Sun et al, 2012 ; Urrutia et al, 2013 ; Tan et al, 2016 ; Xiong et al, 2016 ; You et al, 2017 ; Zhang et al, 2017 ).…”
Section: Brain Hepcidin Expression and Mechanisms Of Regulationmentioning
confidence: 99%
“…The fact that LPS and E. coli infection upregulates the levels of hepcidin mRNA and/or protein in the brain shows that HAMP gene expression can also be upregulated by inflammation, as was found outside of the brain. The finding that pretreatment with hepcidin reduces Aβ treatment‐induced IL‐6 expression and secretion in astrocytes and microglia and reduces neurotoxicity and oxidative damage triggered by conditioned media obtained from Aβ‐treated astrocytes and microglia imply that hepcidin can downregulate inflammatory and prooxidant processes .…”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 83%
“…The finding that pretreatment with hepcidin reduces Aβ treatment‐induced IL‐6 expression and secretion in astrocytes and microglia and reduces neurotoxicity and oxidative damage triggered by conditioned media obtained from Aβ‐treated astrocytes and microglia imply that hepcidin can downregulate inflammatory and prooxidant processes . Recent studies have also demonstrated that intracerebroventricular injection of LPS can upregulate hepcidin expression and also downregulate Fpn1 levels in the cortex and substantia nigra of the rat brain. LPS was able to increase neuronal hepcidin expression only when neurons were cocultured with BV‐2 microglia, and this upregulation was suppressed by IL‐6 neutralizing antibody in vitro.…”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%
See 1 more Smart Citation